PELATIHAN PENGGUNAAN APLIKASI MENDELEY BAGI MAHASISWA PGSD TINGKAT AKHIR DI INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Pransisca, Made Ayu; Pahru, Syaipul; Gazali, Munawir; Habibi, Muhammad Ridwan; Yuliani, Meri; Marzuki, Ahmad Dedi; Hadi, Samsul; Irzan, Muhamad; Mastum, Mastum (LPPM Institut Pendidikan Nusantara Global, 2023)
The participants in this community service activity were PGSD students at the Nusantara Global Institute of Education, especially students who were in the process of compiling scientific papers. This PKM activity uses lecture, practice and question and answer methods. Based on the results of this training activity it was found that during the Mendeley training activities the participants were very enthusiastic as can be seen from the responses of the participants who actively asked when they experienced difficulties. From the results of discussions conducted with students, it was clear that making a list of references was indeed an obstacle for them. Therefore, the PKM implementation team wanted to motivate students that training in using the Mendeley application could help make it easier for them to enter reference lists automatically.